Implementasi Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil, Dan Menengah Pada UMKM Binaan Dinas Koperasi UKM Dan Perdagangan Kota Surabaya : Studi Pada Bengkel Kriya Daun 9996 Surabaya - Faradina Aprilia Putri; Maulidah Narastri (International Forum of Researchers and Lecturers, 2024)
Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM) are prepared to meet the financial reporting needs of micro, small and medium entities. This research is intended to find out how the implementation of accounting based on SAK EMKM on the financial reports of Micro, Small and Medium Enterprises in the City of Surabaya. This study uses a qualitative descriptive research method. Collection is obtained by using interviews and documentation. The conclusion from this study is that informants have not fully used SAK EMKM in their financial reports and there are names that are not appropriate, such as business profit/loss performance, balance sheets, routine expenses and items that are not in accordance with SAK EMKM provisions. This is due to the low sense of interest in preparing financial reports and the lack of counseling about SAK EMKM for MSMEs.